2017
DOI: 10.1103/physrevlett.118.116401
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Dependent Chirality Effects in Quasifree-Standing Graphene

Abstract: We present direct experimental evidence of broken chirality in graphene by analyzing electron scattering processes at energies ranging from the linear (Dirac-like) to the strongly trigonally warped region. Furthermore, we are able to measure the energy of the van Hove singularity at the M point of the conduction band. Our data show a very good agreement with theoretical calculations for free-standing graphene. We identify a new intravalley scattering channel activated in case of a strongly trigonally warped co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…2) due to the presence of low energy van Hove singularities or quasi-localized states which can be seen in Fig. 7(c), similar to the experimentally confirmed 56 broken chirality close to the van Hove singularities of monolayer graphene. Vacancies will therefore have a strong effect and suppress the conductivity at all energies, even at the Dirac point, as can be seen Fig.…”
Section: Disorder Effectssupporting
confidence: 80%
“…2) due to the presence of low energy van Hove singularities or quasi-localized states which can be seen in Fig. 7(c), similar to the experimentally confirmed 56 broken chirality close to the van Hove singularities of monolayer graphene. Vacancies will therefore have a strong effect and suppress the conductivity at all energies, even at the Dirac point, as can be seen Fig.…”
Section: Disorder Effectssupporting
confidence: 80%
“…While our numerical calculations of the spectral function and DOS presented below are based on the full matrix form of the GF in Eq. (22), it is instructive to assume a diagonal form of the self-energy and GF,…”
Section: Quasiparticle Spectrum and Scatteringmentioning
confidence: 99%
“…31,33,140,141 In a recent work on disordered Li-decorated graphene, 88 we demonstrated that in T -matrix descriptions of adatoms (we expect that the same holds for other types of adatoms and adsorbates), it is essential to express the T matrix and the Dyson equation in Eqs. (19) and (22) in a "complete" Bloch-state basis; i.e., the basis must include bands which describe the electronic structure of both graphene and the surface region where the adatoms are located.…”
Section: Adatoms and Adsorbatesmentioning
confidence: 99%
“…In MoS 2 with almost isotropic energy contours, ε(k) = ε, intravalley backscattering with q = 2k therefore produces circular features. Trigonal warping of the constant energy surfaces gives rise to additional approximate nesting vectors which produce starlike patterns with hexagonal symmetry around the Γ point and triangular symmetry near the K, K points as in graphene [30]. feature because intravalley processes in the K and K valleys add up, while the two K ↔ K intervalley processes have distinct wave vectors, q ≈ ±K.…”
mentioning
confidence: 99%
“…The measured STS map is a probe of the local density of states (LDOS) whose real-space modulation, resembling Friedel oscillations, originates from quasiparticle interference (QPI) between electronic waves scattered by defects. Hence, the Fourier transform of the STS map provides direct access to the available scattering channels in q space, and has shed important light on defect scattering in, e.g., graphene [23][24][25][26][27][28][29][30], monolayer TMDs [18,19], and black phosphorus [31].…”
mentioning
confidence: 99%